Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/genes11020208
|View full text |Cite
|
Sign up to set email alerts
|

Cas3 Protein—A Review of a Multi-Tasking Machine

Abstract: Cas3 has essential functions in CRISPR immunity but its other activities and roles, in vitro and in cells, are less widely known. We offer a concise review of the latest understanding and questions arising from studies of Cas3 mechanism during CRISPR immunity, and highlight recent attempts at using Cas3 for genetic editing. We then spotlight involvement of Cas3 in other aspects of cell biology, for which understanding is lacking—these focus on CRISPR systems as regulators of cellular processes in addition to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 94 publications
1
24
0
Order By: Relevance
“…Current evidence supports a model in which Cas3 nicks the DNA at the R-loop, loads onto the ssDNA, and processively unwinds and degrades DNA in a unidirectional and ATP-dependent manner ( Fig. 2A) (19,33,49). Structures of T. fusca Cascade bound to a DNA target and Cas3 revealed that a protruding "bubble" in the nontarget strand of the R-loop is required for Cas3 to nick the DNA ( Fig.…”
Section: Rna-guided Dna Binding and Cleavage By Type I Crispr-cas Syssupporting
confidence: 72%
See 2 more Smart Citations
“…Current evidence supports a model in which Cas3 nicks the DNA at the R-loop, loads onto the ssDNA, and processively unwinds and degrades DNA in a unidirectional and ATP-dependent manner ( Fig. 2A) (19,33,49). Structures of T. fusca Cascade bound to a DNA target and Cas3 revealed that a protruding "bubble" in the nontarget strand of the R-loop is required for Cas3 to nick the DNA ( Fig.…”
Section: Rna-guided Dna Binding and Cleavage By Type I Crispr-cas Syssupporting
confidence: 72%
“…Formation of the R-loop induces a conformational change in the complex that enables recruitment of Cas3, a helicase-nuclease protein that is required for target DNA degradation ( Fig. 2A) (19,20,48). Current evidence supports a model in which Cas3 nicks the DNA at the R-loop, loads onto the ssDNA, and processively unwinds and degrades DNA in a unidirectional and ATP-dependent manner ( Fig.…”
Section: Rna-guided Dna Binding and Cleavage By Type I Crispr-cas Sysmentioning
confidence: 91%
See 1 more Smart Citation
“…Another Cas protein is Cas3, and this Cas protein participates in the CRISPR intervention in the third stage of CRISPR immunity (He et al, 2020[ 45 ]) and is essential for phage defense in the CRISPR-Cas system (Jackson et al, 2014[ 57 ]). While scientific research on the CRISPR-Cas9 system continues, the importance of Cas proteins continues to be discovered.…”
Section: Mechanisms Of Genome Editing Toolsmentioning
confidence: 99%
“…Recognition of PAM and the ‘seed’ reaction by Cascade trigger formation of an R-loop (‘RNA-loop’) complex in which Cascade base-pairs crRNA with a ‘targeted’ strand of DNA duplex, and the other ‘non-targeted’ DNA strand is displaced as ssDNA [ 16 ]—the importance of R-loops in biology is reviewed recently in [ 17 ]. In CRISPR systems, Cas3 is recruited to the Cascade R-loop complex and degrades DNA, processes reviewed recently in [ 18 ]. Therefore, Cas3 destroys MGE DNA and in the process generates DNA fragments that may prime adaptation [ 19 ], by their capture and integration into CRISPR DNA, completing a virtuous cycle of CRISPR activities.…”
Section: Introductionmentioning
confidence: 99%